Faktor – Faktor Yang Mempengaruhi Struktur Modal Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia Periode 2014 – 2016 - Budhi Gunawan (Universitas Tarumanagara, 2019)
This study analyzes the factors that affected the capital structure of chemicals and basic industry sectors from manufacturing companies which were listed on the Indonesia Stock Exchange during 2014-2016. The study were conducted by examining the effect of firm size, liquidity, profitability, business risk, and asset structure on capital structure. This data were collected from the financial report of 27 manufacture basic industry and chemicals sectors which were listed on Bursa Efek Indonesia in 2014-2016. The multiple regressions analysis and classic assumption test have been performed by sing SPSS 22.0 version statistic test instrument. The result of the research shows that the research regression model has fulfilled the requirements there are no symptoms of multicollinearity, heteroscedasticity, and correlation and the in used file is normally distributed. The result of the research shows: profitability, firm size, liquidity, business risk, asset structure has significant influence to the capital structure.